OUTER MEMBRANE PROTEIN OF PORPHYROMONAS GINGIVALIS AS BASIC OF DIAGNOSTIC TOOL IN AGGRESSIVE PERIODONTITIS: PROTEIN MEMBRAN BAGIAN LUAR PORPHYROMONAS GINGIVALIS SEBAGAI ALAT DIAGNOSTIK PERIODONTITIS AGRESIF - Desi Sandra Sari; Candra Bumi; Yuliana Mahdiyah DA (Dentika: Dental Journal, 2011)
Porphyromonas gingivalis is a gram-negative anaerobic bacteria and has been shown previously to be one of the major pathogens in aggressive periodontitis. Outer membrane protein is the major virulence factor of P. gingivalis and plays role in the host immune response impair againts P. gingivalis, which in turns, causing tissue destruction and bone resorption. This study was aimed to investigate the isolation and characteristic outer membrane protein of P. gingivalis. Protein of OMP P. gingivalis ATCC 33277 was isolated using sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) and than continued by hemaglutination test. The result showed that protein profil in SDSPAGE of OMP protein was 40 kDa molecular weight dan hemaglutination test was positive in titer of hemaglutination 1/8.In conclusion, outer membrane protein molecular mass of 40kDa produced by P. gingivalis is a key virulence factor involved in the co-aggregation activity of P. gingivalis